(untitled) (Bangladesh Journal of Zoology, 2019)
Rhizopertha dominica (F.) (Coleoptera: Bostrichidae) is an internal feeder of whole wheat seed, flour, etc. R. dominica is parasitized by two pteromalid ectoparasitoids, Anisoptetromalus calandrae (How.) and Choetospila elegans (Westw.) in the larval and pupal stages. The effects of host density and temperature on the functional response of the parasitoids in parasitizing the larval and pupal stages of the hosts were examined. Four temperatures and five host densities were used. A functional response equation was used in which a quadratic component that included temperature was substituted for handling time. Functional response of parasitization by A. calandrae and C. elegans fit a formula of Hassell et al. (1977) type III model. The maximum rate of parasitization of A. calandrae was 8.6 larvae/24 hrs and 7.2 larvae/24 hrs of C. elegans at 30ºC, respectively. Handling time and instantaneous search rate varied with temperatures. The ability of A. calandrae and C. elegans to find and parasitize R. dominica over a broad range of temperatures demonstrate it as a good candidate for natural control of the pest. Bangladesh J. Zool. 47(1): 41-47, 2019